Nutritional Preference and Attraction of Honey Bee Workers to Some Pollen Substitutes and Liquid and Dry Dietary Supplements to Nourish the Colonies and Increase Their Activity (NTU Journal of Agriculture and Veterinary Science, 2025)
The study was conducted at an apiary in Nineveh Province during the summer of 2023-2024. The results indicated that all liquid and dry alternatives and supplements of honey and pollen had an attractive effect on worker bees, with varying degrees of attraction to all the liquid materials and supplements. The super protein treatment, the mixture, and whey showed the highest attraction rates, especially on the third day of feeding during the evening, with averages of 4355, 3127, and 2525 workers/two hours, respectively. In contrast, the whey treatment recorded an average attraction of 369 workers/two hours, compared to the sugar solution treatment, which recorded the lowest attraction rate with an average of 115 workers/two hours. The results also confirmed that all dry food materials and supplements attracted worker bees to varying degrees, with treatments of palm pollen, the mixture, soybeans, and reishi mushrooms recording the highest averages of 451.7, 376.7, 246.3, and 128 workers/two hours, respectively, compared to the commercial pollen treatment, which attracted fewer bees with an average of 95.3 workers/two hours. The results indicated that evening feeding times recorded higher attraction rates than morning times, with averages of 184.8 and 159.3 workers/two hours, respectively.